Molecular Layer Deposition of Organic-Inorganic Hafnium Oxynitride Hybrid Films for Electrochemical Applications - Ablat, Hayrensa; Oh, Il Kwon; Richey, Nathaniel E.; Oyakhire, Solomon T.; Yang, Yufei; Zhang, Wenbo; Huang, William; Cui, Yi; Bent, Stacey F. (ACS Applied Energy Materials, 2023)
The molecular layer deposition (MLD) method can be used to deposit hybrid organic-inorganic films with precisely defined composition, flexible properties, and conformality on different substrates. In this study, hafnium-based organic-inorganic hybrid polymer films were studied as potential coatings for silicon nanoparticles (SiNPs) used in composite lithium-ion battery (LIB) anodes, an application which requires the film to be both flexible and stable under electrochemical conditions. Hf-hybrid films were successfully deposited by MLD using sequential exposure of the homoleptic tetrakis(dimethylamido) hafnium complex and ethanolamine as the reactants. The self-limiting surface reactions lead to a constant growth per cycle (GPC) of ∼2.0 Å/cycle at 120 °C. Temperature-dependent growth was observed, with the GPC decreasing from ∼2.5 to ∼1.1 Å/per cycle as the temperature was increased from 65 to 145 °C. Scanning transmission electron microscopy and electron energy loss spectroscopy mapping confirm that a thin, dense, and conformal Hf-based MLD layer is deposited on the SiNPs. The presence of expected C-N, C-O, and −CH2 moieties in the MLD films was confirmed by Fourier transform infrared spectroscopy. Hafnium nitride and hafnium oxide bonds within the hybrid thin films were identified by X-ray photoelectron spectroscopy. Characterization results indicated that the deposited hafnium-based organic-inorganic hybrid films contain both metal oxynitride bonds and organic bonds, including C-C, C-O, and C-N. This Hf-based MLD thin film was tested on LIB SiNP composite anodes as an artificial solid-electrolyte interphase, with results showing that the capacity retention increased by about 35% after 110 cycles in a LIB application.
Keywords: Artificial solid-electrolyte interphase; Composite anodes; Growth per cycle; Hafnium oxynitride; Hafnium oxynitride hybrid film; Hybrid film; Molecular layer deposition; Silicon nanoparticle composite anode; Silicon nanoparticles; Solid electrolyte interphase; artificial solid-electrolyte interphase; hafnium oxynitride hybrid film; Li-ion battery; MLD; SiNP composite anode